2023
DOI: 10.2174/1567202620666230303144323
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Alleviates Oxidative Stress, Neuroinflammation, and Promotes Behavioral Recovery After Traumatic Brain Injury

Abstract: Background: Neuroinflammation and oxidative stress after traumatic brain injury (TBI) can further lead to neuronal apoptosis, which plays a crucial role in the process of neuron death. Curcumin, which is derived from the rhizome of the Curcuma longa plant, has multiple pharmacological effects. Objective: The objective of this study was to investigate whether curcumin treatment has neuroprotective effects after TBI, and to elucidate the underlying mechanism. Methods: A total of 124 mice were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Considerable evidence supports the involvement of oxidative stress and inflammation in the pathophysiology of memory impairments following TBI (Bing et al., 2023 ; Chen et al., 2017 ). Recent studies have demonstrated that persistent oxidative stress and neuroinflammation are commonly observed in the hippocampus of TBI, and inhibiting oxidative stress and neuroinflammation has been associated with the improvement of cognitive dysfunction (Wang et al., 2020 ; Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…Considerable evidence supports the involvement of oxidative stress and inflammation in the pathophysiology of memory impairments following TBI (Bing et al., 2023 ; Chen et al., 2017 ). Recent studies have demonstrated that persistent oxidative stress and neuroinflammation are commonly observed in the hippocampus of TBI, and inhibiting oxidative stress and neuroinflammation has been associated with the improvement of cognitive dysfunction (Wang et al., 2020 ; Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…These findings provide a fresh perspective on TBI treatment, underscoring the need for a multifaceted approach to tackle different facets of neuronal damage and recovery. Inhibiting processes like neuroinflammation and oxidative stress can aid in preventing neuronal loss and reducing brain tissue damage, thus lowering the risk of neurodegeneration [109,110].…”
Section: Multifaceted Approaches To Traumatic Brain Injury (Tbi) Trea...mentioning
confidence: 99%